EFFICIENCY OF FLUORESCENCE IMAGING IN LOCALISATION OF ORAL LESION AT RISK OF MALIGNANCY - Buștiuc Steliana-Gabriela; Caraiane Aureliana; Bordeianu Ion; Raftu Gheorghe; Sin Elena-Claudia; Petcu Lucian Cristian (Romanian Society of Oral Rehabilitation, 2021)
Aim of the study The aim of this study is to evaluate the efficacy of autofluorescence in localisation of oral mucosal lesions at risk of malignancy. Material and methods 72 patients with oral lesions were examined using conventional light and the Oral ID device, complementing the conventional light examination. Results The concordance between the conventional light (CL) examination method and the examination method using the device based on the fluorescence of the oral mucosa was 88.9% with a Kappa coefficient of 0.755 for the tongue localization, 84.7% with a Kappa coefficient with the value 0.627 for the cheek localization, 97.3% with a Kappa coefficient with the value 0.911 for the oral floor localization, 100% with a Kappa coefficient with the value 1 for the palate and alveolar ridge localization, 97.2% with a coefficient Kappa with a value of 0.819 for the lower lip location, 98.6% with a Kappa coefficient with the value of 0.793 for the upper lip location. The average concordance between the two examination techniques is 95.24% with a Kappa coefficient with an average value equal to 0.84.Conclusions The concordance between the two examination methods was good for all the sites considered in this study. The use of the visualization method based on florescence of the oral mucosa improved the detection of oral lesion with locations difficult to examine under conventional light.